The effect of hormone type and amount of dose on gonadotropin hormones levels in blood plasma of common carp (Cyprinus carpio) during artificial spawning processes - Al Zaidy, Faleh, M.; Al-Noor, Sajed S.; Jasim, Basem M. (Iraqi Journal of Aquaculture, 2021)
The study included the utilization of three types of hormones, i.e. LHRH-A2 with dosages of 10, 20 or 30 μg / kg, a mixture of LHRH-A2 with dosages of 10, 20, and 30 μg / kg with Domperidone (DOM) at 5 mg / kg and carp pituitary gland extract (CPE) at 3 and 4 mg / kg, in order to study the effect of hormone type and used dosage on the level of gonadotropins secreted from the pituitary gland of the common carp Cyprinus carpio L. females during the artificial fertilization. Concentrations of GTHs (FSH and LH) were measured using ELISA kit on blood samples collected from fish caudal peduncle after 2, 6 and 12 hours of injection with LHRH-A2 and hormone mixture or 2, 6 and 8 hours for fish treated with CPE .Results showed that GTHs levels were low in fish treated with LHRH-A2 for all the utilized dosages LH (4.66 ± 1.27 mIU / mL) or LHRH-A2+ DOM LH (5.22 ± 0.77 mIU / mL). In contrast, GTHs levels in fish treated with CPE at 3 and 4 mg / kg were higher and levels of FSH and LH were higher with 4 mg / kg LH (34.51 ±12.59 mIU/mL) than it with 3 mg / kg,